2021
DOI: 10.1051/0004-6361/202140563
|View full text |Cite
|
Sign up to set email alerts
|

Why do more massive stars host larger planets?

Abstract: Aims. It has been suggested that planetary radii increase with stellar mass for planet sizes smaller than 6 R⊕ and host masses lower than 1 M⊙. In this study, we explore whether this inferred relation of planetary size and host star mass can be explained by a higher planetary mass of planets orbiting higher-mass stars, inflation of the planetary radius due to the difference in stellar irradiation, or different planetary compositions and structures. Methods. Using exoplanetary data of planets with measured mass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
3
7
0
Order By: Relevance
“…The higher efficiency allows them to accrete a substantial gaseous envelope before the gas disc dissipates. The results shown in Figures 13 and 14 confirm the finding of Lozovsky et al (2021), extending them at higher stellar effective temperatures. For F stars, Pascucci et al (2018) expected that the presence of other effects, such as atmospheric loss by photoevaporation, might affect the properties of their planetary systems.…”
Section: Relations With the Characteristics Of The Planetsupporting
confidence: 77%
See 2 more Smart Citations
“…The higher efficiency allows them to accrete a substantial gaseous envelope before the gas disc dissipates. The results shown in Figures 13 and 14 confirm the finding of Lozovsky et al (2021), extending them at higher stellar effective temperatures. For F stars, Pascucci et al (2018) expected that the presence of other effects, such as atmospheric loss by photoevaporation, might affect the properties of their planetary systems.…”
Section: Relations With the Characteristics Of The Planetsupporting
confidence: 77%
“…Pascucci et al (2018), focusing on GKM stars, showed that the radius of the planets depends on the mass of the stellar host. Very recently, Lozovsky et al (2021) confirmed the tendency, and explored the reasons for which more massive stars host larger planets. While the hypothesis bases on thermal inflation and on the effect of planet mass on the radius are less favourable, Lozovsky et al (2021) concluded that planets around more massive stars tend to be richer in gas and are, therefore, larger.…”
Section: Relations With the Characteristics Of The Planetmentioning
confidence: 90%
See 1 more Smart Citation
“…initial atmospheric mass fraction vs. either planetary or stellar mass and semi-major axis) that would enable planetary accretion models, and thus planet formation to be empirically constrained (e.g. Lozovsky et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The connection between planetary origin and internal structure is nontrivial, and different formation mechanisms and birth environments can lead to a large range of compositions and internal structures (e.g., Helled et al 2014;Lozovsky et al 2017;Valletta & Helled 2020 and references within). Even the host stellar type might influence the planetary structure and composition (Silva & Valio 2016;Adibekyan et al 2021;Lozovsky et al 2021). While there are numerous observations of protoplanetary disks (e.g., Andrews 2020), and various aspects of their evolution have been modeled theoretically, the properties of such protoplanetary disks are still not well constrained.…”
Section: Introductionmentioning
confidence: 99%